PROBLEMS AND OPPORTUNITIES OF THE NATIONAL MARKET OF FRESH FLOWERS - KRUTYAK, David; DEMIDCHUK, Lyudmila (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses the issues of floristic business in Ukraine, which is going through hard times, which is directly related to the crisis and the situation in the country and has led to a drop in demand for fresh flowers, which play the role of a kind of barometer of the well-being of society. The basis of global trade and floristic services is made up of cut flowers, which are the most transportable products. The purpose of the study was to examine the current challenges and opportunities for the effective development of the fresh (cut) flower market in Ukraine.The article shows that domestic floriculture should follow its own path, based on competitive production conditions, technical equipment of farms, cost/income ratio, and sales opportunities. Bulbous crops are so profitable in our country that the demand for planting material is growing steadily. Ukraine is increasingly buying rooted cuttings of potted and garden plants. The trend towards the progressive development of domestic floriculture is also justified by the growing of fashionable potted flowers from imported semi-finished products, as evidenced by the purchase of more and more planting material for cut and pot products. Only a reasonable combination of imports and domestic production, taking into account the energy intensity of crops and market demand, will make the national market civilized.The main reasons for the pushing of Ukrainian producers out of the flower market are highlighted, including the lack of modern technologies. Flowers grown in Soviet greenhouses built using old technologies are far inferior in quality to those imported from abroad and cannot satisfy the buyer, while prices for Ukrainian and imported flowers often coincide; lack of funding for breeding new species and hybrids of flowers; stereotypical belief of the majority of the population that domestic flower products are far inferior to imported ones in quality.It is concluded that the optimal way for the domestic flower industry to go is to produce seedlings, potted plants and those crops that do not require significant costs. The widespread use of imported cuttings is economically justified for those types of flowers that are expensive and energy-intensive to grow in Ukraine. At the same time, focus on the production of those crops where Ukraine is the undisputed leader, which is largely determined by historical and climatic factors.
Keywords: flower market; production; floriculture; imports; world division of labour; potential; prospects